Proceedings of the International Conference on Economics and Banking 2015 2015
DOI: 10.2991/iceb-15.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Green Banking : One Effort To Achieve The Principle Of Good Corporate Governance (GCG)

Abstract: Environmental damage that occurs in most of the Earth causing environmental movement nowadays in various fields with the term green, eco. One of them is in banking. Implementation of green banking holds the principle of sustainable development that development should have a balance on three viewpoints (Triple Bottom Line), they are Profit (Economy), People (Social) and Planet (Safe Environment). Business sustainability in the future must be achieved, the value of the company increase and grow rapidly also it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Jizi et al () examine the disclosure of U.S. banks and found a positive association between board characteristics (independent directors and board size) and bank's environmental performance. However, implementation of green banking holds the principle of sustainable development (Dialysa, ), which may derive through two core reinforcements ‐ corporate governance compliance and firm‐specific needs. Researchers present evidence of corporate governance effects on firms' environmental issues and innovation (Amore, Bennedsen, & Nielsen, ; Bunget et al, ; Clark, ; Dialysa, ; Iraldo, Testa, & Frey, ; Radu, ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Jizi et al () examine the disclosure of U.S. banks and found a positive association between board characteristics (independent directors and board size) and bank's environmental performance. However, implementation of green banking holds the principle of sustainable development (Dialysa, ), which may derive through two core reinforcements ‐ corporate governance compliance and firm‐specific needs. Researchers present evidence of corporate governance effects on firms' environmental issues and innovation (Amore, Bennedsen, & Nielsen, ; Bunget et al, ; Clark, ; Dialysa, ; Iraldo, Testa, & Frey, ; Radu, ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, past studies have ignored the governance structure of (Dialysa, 2015), which may derive through two core reinforcements -corporate governance compliance and firm-specific needs. Researchers present evidence of corporate governance effects on firms' environmental issues and innovation (Amore, Bennedsen, & Nielsen, 2015;Bunget et al, 2009;Clark, 2015;Dialysa, 2015;Iraldo, Testa, & Frey, 2009;Radu, 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Deadly bush fires, withering coral reefs, rising sea levels, and ever more cataclysmic storms are amongst the negative impacts of the decision by banks to support projects unfavourable to the environment (Ewing, 2020). Further, the environmental problems caused by some of these problems have been shown to lead to increases in stress, disgust, anxiety, and worry in people, which reduces public well‐being (Atik, Fırat, Ozgun, & Uzunoğlu, 2020; Doherty & Clayton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Following the negative impacts of environmental degradation, banking customers have demonstrated interest in green banking, a type of banking that respects environmental issues in their operation. This interest has appeared in developed countries, such as Greece (Lymperopoulos, Chaniotakis, & Soureli, 2012) and France (Park & Kim, 2020), as well as in developing countries such as India (Bryson, Atwal, Chaudhuri, & Dave, 2016) and Indonesia (Dialysa, 2015). Missing from previous studies on green banking (Bryson et al., 2016; Lymperopoulos et al., 2012) is the role of emotion with moral perspective in driving behavioural intention (Antonetti & Baines, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only the path from green compliance to benefits has a moderate effect (f square=0.17, which is greater than 0.15), whereas the other two paths indicate a weak effect (less than 0.02) (Chin, 1998;Cohen,1988;Hair et al, 2014). In the literature, we found that some researchers (Clark, 2015;Dialysa, 2015;Radu, 2012;Iraldo et al, 2009;Amore et al, 2015;Bunget et al, n.d.) indicated a relationship between good governance and better environmental performance. In line with this, independent directors positive association with the board provides support for hypothesis H1b, which is also backed by many other studies (Mittal, 2011, De Andres & Vallelado, 2008, Shakir, 2008.…”
Section: Discussionmentioning
confidence: 86%